HUBUNGAN DINAMIS ANTARA INDEKS HARGA SAHAM DAN NILAI TUKAR DALAM MASA KRISIS EKONOMI DI INDONESIA - FIRMAN PRIBADI; JOGIYANTO HARTONO (Jurnal Bisnis dan Akuntansi, 2004)
This research uses econometric advanced and Error Correction Model (ECM) for testing inter temporal relation between stock price index and exchange rate with using daily data. ECM is used at two variables for estimating as simultaneous dynamic relation between both financial markets. The results of ECM estimation showing the existing two direction or relationship mutual influence between both financial markets. In the short time stock price aggregate has negative effect at exchange rate and exchage rate has positive effect and negative at aggregate to stock price. In the long term stock price has negative effect to exchange rate and exchange rate has positive effect at stock market. By this research can be concluded that at this crisis time rupiah exchange rate has influence more biger at stock price compare stock price index toward rupiah. This case can be see from the big of EC-term at both level.